WAYS OF TEACHING LINGUISTIC TERMINOLOGY IN ENGLISH LANGUAGE CLASSES TO STUDENTS OF 5-9 GRADES - Valikulova Dildora (Innovate Conferences, 2025)
The article is about the ways of teaching linguistic terminology of the English language at school to the students of 5-9 grades. The writer explains the role of linguistic terminology in foreign language learning, accepting it as a significant component of the metalinguistic skills of learners.
Keywords: foreign language, metalinguistic skills, English, linguistic terminology, blitz quiz, word dictation, matching, word scramble, classification activity, gap-fill.